Experimental Study of Silty Clay Plane Strain Tri-axial Test under RTC Path and Modified Cam-clay Model - Cheng, Tao; Zhang, Yi; Yan, Keqin (Salehan Institute of Higher Education, 2018)
The character of geomaterials is affected by stress path remarkably. Under different stress paths, the stress-strain characteristics of geomaterials are difference. For the unloading path in existing engineering situation, the physical parameters and constitutive model is usually determined by loading test. The path to uninstall the actual project conditions which may be a larger error. Therefore, this work proceeding from the actual project, deep excavation of the lateral unloading condition is analysed. The tests of CTC path and RTC path on silty clay in Huangshi city of china by multi-path tri-axial plane strain are carried on in the geotechnical Engineering Laboratory of Huangshi Institute of Technology. Then, the phenomenon under the two stress paths are compared with each other and describing the differences between them. The mechanical properties in the RTC stress path is analyzed mainly. Based on the Cam-Clay model framework, then derived this material yield equation based on Cam-clay model, Laiding the foundation for the numerical analysis.